Child and caregiver issues in the treatment of attention deficit––hyperactivity disorder: education, adherence and treatment choice. (May 2011) - Ferrin, Maite; Taylor, Eric
There is much more to successful drug treatment than writing a prescription. In this article, we describe some of the ''holistic'' aspects of the pharmacological treatment of attention deficit––hyperactivity disorder, with an emphasis on helping families to decide between psychological and pharmacological treatment and on the process of psychoeducation. Detailed accounts of drug and behavioral treatment in various circumstances are available elsewhere; however, the value and process of psychoeducation is sometimes underestimated or referred to in a cursory statement of the need for a good doctor––patient relationship. There has been little in the way of controlled trials, so no meta-analysis is attempted. Where possible (e.g., in reviewing the effects of psychological therapy and prediction of drug response), PubMed/Medline was searched for systematic reviews and randomized trials, but this article''s conclusions should be taken as personal. These subjective views are based chiefly on experience in clinical practice, participation in focus groups with young people and their families and work with support groups.